Assessment of nutrition education strategies to reduce cardiovascular disease in U.S. Army hospitals - Bukhari, Asma Sultana, author; Anderson, Jennifer, advisor; Kaminski, Karen, committee member; Gould, Susan, committee member (Colorado State University. Libraries, 2007)
Cardiovascular disease (CVD) continues to be the leading cause of death in the United States with an estimated 79,400,000 adults diagnosed with this disease in 2004 and costs of $431.8 billion projected this year. As a result there is an increased emphasis on early detection and treatment of risk factors. Military personnel are vulnerable to this killer disease due to indulgence in unhealthy behaviors such as cigarette smoking, physical inactivity, poor nutrition, and increased stress. These behaviors can have a profound impact on the military readiness and mission accomplishment. The purpose of this study was to identify strategies to enhance nutrition education provided to the military personnel at US Anny hospitals to manage CVD. The results will be used to identify weaknesses and gaps in an existing program and facilitate improvement of CVD nutrition education. It was hypothesized that nutrition education can be enhanced by aligning the existing CVD management programs with evidenced based guidelines that will provide program consistency. The target audience for this study was Registered Dietitians in clinical leadership positions at U.S Anny hospitals and outpatient clinics. The study was approved by the Colorado State University Human Research Committee and the U.S Anny Medical Research and Material Command Human Research Protection Office. Survey validity was established by obtaining information from a review of literature and feedback from expert Army dietitians and CSU faculty. Survey reliability was established by a test and re-test during a pilot test on a subset of Army dietitians. The responses were analyzed using computer software and reported as mean, standard deviations and frequencies. The survey response rate was 70% (n=21). The primary educators of CVD risk reduction were dietitian. Sixty-two percent of the hospitals provided nutrition education based on current guidelines. The current program was rated either "very good" or "good" by 67% of the dietitians. Eighty-one percent of dietitians experienced variation in the program at their hospitals. Only 24% of the dietitians indicated a mechanism to reach deployed soldiers with hypercholesterolemia. A web-based resource center was selected by 43% of the dietitians followed by 23% who suggested development of a self-paced web-based education program for deployed or remotely located soldiers. Caution is advised while interpreting the results because the findings are based on dietitians' knowledge and opinions and may not have captured all the services offered to the patients. The survey provided insight into current program and suggestions for future program improvements. Cost effectiveness and improved patient satisfaction of medical nutrition therapy by Registered Dietitians is already established. Army dietitians need to take the lead in designing and implementing programs to reduce the CVD risks among military personnel. Such interventions will improve the quality of life of soldiers by providing long term health benefits; and that, in tum, will save resources from reduction in mortality and morbidity associated with CVD events. It is important to explore various communication media for information dissemination.
Keywords: United States Army Medical Service; Military hospitals -- Cardiovascular services -- United States; Military hospitals -- Cardiovascular services; Cardiovascular system -- Diseases -- Nutritional aspects; Nutrition counseling -- United States; Nutrition counseling; United States